Предмет: Алгебра,
автор: дло987про543
при каком значении переменной выражения 6-(2x-9) и (18+2x)-3(x-3) принимают равные значения?
Ответы
Автор ответа:
0
6 - (2x-9) =(18+2x) - 3(x-3);
6 - 2x + 9 = 18+2x - 3x +9;
- 2x + 15 = - x + 27;
- 2x + x= 27- 15;
- x = 12;
x = - 12.
6 - 2x + 9 = 18+2x - 3x +9;
- 2x + 15 = - x + 27;
- 2x + x= 27- 15;
- x = 12;
x = - 12.
Похожие вопросы
Предмет: Английский язык,
автор: babylovepersik
Предмет: Математика,
автор: noell11
Предмет: Физика,
автор: michaelli
Предмет: Математика,
автор: ВиКиСя
Предмет: История,
автор: KostinaYa